Faktor yang Berhubungan dengan LOS Pasien Bedah Orthopedi - Rahman, Abdul; Ibrahim, Kusman; Rahayu, Urip (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This literature review aims to analyze what factors are associated with LOS in orthopedic surgery patients. This literature review was carried out using PRISMA guidelines, the electronic databases used were ScienceDirect, CINAHL and Pubmed with the keywords